2021
DOI: 10.25259/ijpp_77_2020
|View full text |Cite
|
Sign up to set email alerts
|

Nerve conduction velocities in radiologic technologists: A pilot study

Abstract: Objectives: Radiologic technologists (RTs) are typically exposed to low doses of radiations for longer periods, which have a health risk over many organs and tissues. Resistant tissues like nerves have shown neuropathic changes due to acute high-dose radiation exposure in the form of radiation therapy but the effect of low-dose chronic radiation exposure over peripheral nerves in RTs has been studied scantily. Materials and Methods: Nerve conduction parameters were recorded from 30 RTs and 30 age- and sex-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…According to a survey report, smartphone usage increased by 50 % and was one of the profound reasons for smartphone addiction in teens [1]. Different pathological processes result in changes in NCS parameters [8]. A study report demonstrated that median motor nerve electrophysiological findings were strong predictors of the results of hand-function tests in the hand osteoarthritis patient population [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to a survey report, smartphone usage increased by 50 % and was one of the profound reasons for smartphone addiction in teens [1]. Different pathological processes result in changes in NCS parameters [8]. A study report demonstrated that median motor nerve electrophysiological findings were strong predictors of the results of hand-function tests in the hand osteoarthritis patient population [9].…”
Section: Introductionmentioning
confidence: 99%